Epistemologia da ciência da informação: um estudo das comunicações da GT1 do ENANCIB - Nunes, Lucilene [UNESP] (2009)
The present work proposes to think the development of the research and the innovation of the scientific thought on the field Information Science. In order to reach the achieve this goal we defined as the survey of the annals of ENANCIB (National Meeting on Research in Information Science) specifically, the communications GT1 “Historical Studies and Epistemological Information”, comprehend in the 98 works distributed in six issues included in the research. We intend to also check the extent to presented in this group are in line with the assumptions announced by the matter of concern, trying to identify the subjects of research that has been made over the last eight years on the Postgraduate Programs in Information Science in Brazil. To do so, we highlight the epistemological concerns of researchers in the field. We tried to establish theoretical literature based of the information science, understanding the birth, development, paradigm shifts, and the history of education in Library Science in Brazil, to finally discuss the emergence of Postgraduate Programs and agencies linked to it as the CNPq and CAPES. The method employed this work were based on the fragmentation of the matter of concern of GT1 in seven subject categories, in which was distributed in the 323 keywords in 98 jobs. The conclusions in the end, confirm the GT1 as a space that provides the progress of scientific thought of the area and plays a key role in developing the Field. It is necessary, therefore, due attention in order to prioritize the needs that the field shows, and check the direction to which your research is heading.